PERAN SERIKAT PEKERJA DALAM KESEPAKATAN KERJA BERSAMA (STUDI PADA PT.FUMIRA SEMARANG) - Tia Agustina Faricha; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2019)
This research was conducted at PT.FUMIRA Semarang, aimed at analyzing the role of trade unions as representatives in making Collective Labor Agreements (KKB), the role of trade unions in creating harmonious, dynamic, and fair work agreements as well as the role of trade unions as distributors of aspirations in fighting for labor rights. The results of this study can be concluded that the role of trade unions at PT.Fumira Semarang is categorized as good, it can be seen from the Role of Trade Unions in Making Collective Agreements and the Role in Resolving Industrial Disputes. In this case workers feel that trade unions can be the right place for channeling aspirations and when there are rights that are not fulfilled by the company, the unions have become a forum for workers who are responsible for fighting for, defending and protecting workers' rights and obligations as well as preventing conflicts in industrial relations itself. Maintenance of relations between workers, trade unions and management within the scope of industrial relations is necessary to prevent conflicts in the world of work. Conflicts that are not immediately resolved can lead to cases of industrial relations disputes due to disharmony relations between these parties Suggestions that can be given are 1) trade unions should try more hard to fight for labor right at PT.FUMIRA so as not to be impressed only as a formality institution, 2) there workers or same workers as representative are involved at the time of the review with respect to the contents of the collective labor agreement, 3) the schedule for the payment of wages should not be delayed from the time agreed upon in the agreement.